Cyanoacrylate Dermal Closure in Spine Surgery: Systematic Review and Pooled Analysis. Issue 4 (June 2020) - Tan, Terence; Rutges, Joost; Marion, Travis; Hunn, Martin; Tee, Jin
Study Design: Systematic review. Objectives: Cyanoacrylate glue closure has been utilized for dermal closure in surgical incisions. Its safety and efficacy in spine surgery are not established. The authors perform a systematic review to determine the rate of surgical site infection (SSI), wound dehiscence, and wound erythema with cyanoacrylate dermal closure in spine surgery. Methods: A systematic review adhering to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines was performed utilizing the PubMed/MEDLINE, EMBASE, and Cochrane databases on patients undergoing spine surgery with cyanoacrylate dermal closure. Pooled analysis was performed with stratification of patients according to spinal level and the presence/absence of instrumentation. Risk-of-bias and methodological quality was appraised using 17 prespecified criteria. Results: Five articles (1 retrospective cohort study, 4 cases series) with a total of 1282 patients were included. A total of 967 patients, all diagnosed with degenerative spine disease, were suitable for pooled analysis. In 290 patients who underwent anterior cervical discectomy and fusion, and in 23 patients with posterior cervical decompression (without instrumentation), there was 0% rate of SSI, wound dehiscence, and erythema. In 489 patients who underwent lumbar microdiscectomy, there was 0.41% rate of SSI, 0.20% rate of wound dehiscence, and 0.20% rate of wound erythema. In 165 lumbar laminectomy patients, there was a 1.82% rate of SSI, 0.61% rate of wound dehiscence, and 0% rate of wound erythema. Conclusion: Cyanoacrylate dermal closure for the aforementioned procedures is associated with low rates of wound complications (SSI, dehiscence, and erythema). Further studies should be performed, especially in nondegenerative surgery, instrumented thoracic and lumbar spine surgery.